2021
DOI: 10.1002/fsn3.2134
|View full text |Cite
|
Sign up to set email alerts
|

Differences in energy metabolism and mitochondrial redox status account for the differences in propensity for developing obesity in rats fed on high‐fat diet

Abstract: Obesity is a metabolic disease that is accompanied by oxidative stress. Mitochondrial dysfunction is closely associated with the occurrence and development of obesity. However, it is unclear if there are differences in mitochondrial redox homeostasis and energy metabolism between obesity‐prone (OP) and obesity‐resistant (OR) individuals and if these differences account for the different susceptibilities to developing obesity. The present study aimed to compare the regulation of energy metabolism between OP and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Non-alcoholic fatty liver disease , oxidative phosphorylation, diabetic cardiomyopathy, Alzheimer’s disease ; see Supplemental File 3 ). This suggests that F0 adolescent morphine exposure, even under CD conditions, results in alterations in hepatic transcription consistent with the effects of FSD maintenance 28 . Moreover, many of the pathways identified implicate metabolic and inflammatory processes that are frequently associated with negative health outcomes.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Non-alcoholic fatty liver disease , oxidative phosphorylation, diabetic cardiomyopathy, Alzheimer’s disease ; see Supplemental File 3 ). This suggests that F0 adolescent morphine exposure, even under CD conditions, results in alterations in hepatic transcription consistent with the effects of FSD maintenance 28 . Moreover, many of the pathways identified implicate metabolic and inflammatory processes that are frequently associated with negative health outcomes.…”
Section: Discussionmentioning
confidence: 54%
“…Indeed, Lu et al, recently reported that 8 weeks of high fat diet (HFD) feeding resulted in impaired mitochondrial respiratory function concurrent with dyslipidemia that worsened as the feeding period was extended. Further, while HFD fed males maintained normal glycemia following the 8-week feeding paradigm, prolonged feeding (20 weeks) was sufficient to induce hyperglycemia 28 .…”
Section: Discussionmentioning
confidence: 91%
“…Study groups have worked with the hypothesis that OR is due to a complex interaction of several metabolic factors that are activated to a greater or lesser extent in response to environmental factors, for example, contact and maintenance of a high-fat diet [ 9 , 32 , 33 ]. In this sense, researchers have invested efforts in mapping biomarkers of energy production, storage and consumption systems [ 2 , 4 , 9 , 24 , 29 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the etiology of OR is still unknown in the literature, since its characterization was described more than three decades ago. In this sense, most of the works dedicate efforts to the study of metabolism and metabolic pathways related to the accumulation and/or oxidation of adipose tissue alone [ 2 4 ] or associated with spontaneous physical activity [ 5 7 ], but the study of lipid oxidation pathways in skeletal muscles in models of OR still seem to be scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to the heterogeneity of human obesity, rodents also show two different obesity phenotypes, namely OP and OR 14,15 . Although the baseline weights of these rats are the same, marked differences in food intake, PA, central regulation and peripheral tissue metabolism lead OP rats to become obese after several weeks of receiving a HFD, while OR rats tend to remain at a normal weight [32][33][34] . We established a model of OP and OR rats by using a classic programme involving a HFD 14,15,34 .…”
Section: Hiit Had a Stronger In Uence On Body Weight Vat Mass And Liv...mentioning
confidence: 99%